The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1016/j.jallcom.2007.06.044
|View full text |Cite
|
Sign up to set email alerts
|

A contribution to the Al–Ni–Cr phase diagram

Abstract: The Al-Ni-Cr phase diagram was specified at 1000 • C and partially at 900 • C. The results concerning the region below 60 at.% Al agreed qualitatively with the literature data. The binary Al-Cr phases and ␥ dissolve up to ∼1 and ∼3 at.% Ni, respectively, and Al 3 Ni 2 up to ∼2.5 at.% Cr. Two ternary phases were revealed: hexagonal (a ≈ 1.77, c ≈ 1.24 nm) in a wide range between Al

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
27
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 13 publications
5
27
1
Order By: Relevance
“…(a) The phase s 1 , having the crystal structure reported by Sato et al, [11] is found to have an extended homogeneity range ( Figure 1) closely matching the data of Grushko et al [12] for 900°C. The XRD profile refinements show that the lattice parameters vary little but systematically with composition (Table I).…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…(a) The phase s 1 , having the crystal structure reported by Sato et al, [11] is found to have an extended homogeneity range ( Figure 1) closely matching the data of Grushko et al [12] for 900°C. The XRD profile refinements show that the lattice parameters vary little but systematically with composition (Table I).…”
Section: Resultssupporting
confidence: 79%
“…This phase was labeled e, because it was found to have lattice parameters virtually identical to the reportedly binary phase e-CrAl 4. [13][14][15] This phase did not occur at 900°C, but Grushko et al [12] mentioned the existence of two more ternary phases at lower temperatures without giving further details.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of research [7] indicate the presents of alloys of more complex composition. Thus, combinational manifold of atomic clusters of the Ni-Cr-Al system indicates their considerable disequilibrium and inhomogeneity.…”
Section: Introductionmentioning
confidence: 89%
“…The diagram approach used in the structural-phase analysis of alloys is developed for binary systems including Ni-Cr and Ni-Al systems [3,4]. As for ternary systems, the Ni-Cr-Al system in particular, the interest in research in this area is insignificant and the published results are few in number but they come into notice [5][6][7].…”
Section: Introductionmentioning
confidence: 99%